Legal basis for harmonization of insurance legislation in the conditions of the EAEU - Bayan, М.; Ospanova, Д.А.; Ploczkaya, O.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Within the framework of this article, the issues of transformation of the insurance legislation of the Republic of Kazakhstan in connection with the harmonization of the legislation of the member states of the Eurasian Economic Union (hereinafter – EAEU) are considered. In accordance with the legislation of the EAEU, it is planned to form a common financial market within the EAEU. In this regard, regulatory legal acts regulating public relations in the banking sector, the insurance market and the securities market will be brought into uniform compliance. To achieve the concluded contractual obligations within the framework of the EAEU, Kazakhstan is improving insurance legislation. The author summarizes the regulatory legal framework for the harmonization of insurance legislation, makes conclusions and suggestions for improving the insurance legislation of the Republic of Kazakhstan. The analysis of the legal basis for the harmonization of insurance legislation in the EAEU is important for determining the main directions for improving the insurance legislation of the Republic of Kazakhstan. When harmonizing the insurance legislation of the Republic of Kazakhstan with the relevant legislation of the ECO member countries, it is necessary to take into account the national insurance policy.